Konsep Pembiayaan Mudharabah Dalam Perbankan Syariah - Fauzi, Muhammad (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2023)
Islam is a comprehensive religion that concretely regulates world affairs and also regulates affairs in the hereafter. One of the teachings of Islam that regulates human life is on the economic aspect (muamalah, iqtishadiyah). Islam in the economic aspect is very large. This study aims to determine the extent to which the concept of mudharabah financing in Islamic banking is discussed in a study. There have been many studies and discussions from previous research on the concept of mudharabah financing in Islamic banking or mudharabahl financing. In this study, mapping of themes from previous studies was carried out through literature studies. From a search on the Google scholar database with the keywords "mudharabah financing" AND "mudharabah concept" OR "mudharabah contract" in the period 2019 to 2022, 102 articles were found which were then selected to become 23 articles which were considered still relevant to the theme being discussed. The 23 selected articles are grouped into several themes: 1) Mudharabah financing in Islamic banks. 2) The concept of mudharabah financing. 3) Factors affecting mudharabah financing.